Мислення у догмі різних філософських систем - Тішко, Лілія Володимирівна; Tishko, Liliia (НВЦ «Sci-conf.com.ua», 2024)
У статті досліджується мислення як необхідна здатність людини для виживання. Показано,що у призмі філософського світобачення, мислення є запорукою свободи, а не лише основою суспільного прогресу. Ціллю роботи є дослідження розуміння поняття «мислення» у догмі різних філософських систем. The article examines thinking as a necessary human ability for survival. It is shown that in the prism of the philosophical worldview, thinking is a guarantee of freedom, and not only the basis of social progress. The purpose of the work is to study the understanding of the concept of "thinking" in the dogma of various philosophical systems.
Thinking in the Dogma of Various Philosophical Systems
Keywords: мислення; thinking; світогляд; outlook; світобачення; worldview; філософська система; philosophical system